2004
DOI: 10.1080/07399330490458079
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Knowledge, Attitude, and Practice of Cervical Screening Among Female Primary Care Physicians in the United Arab Emirates

Abstract: Cancer is the third leading cause of death In the United Arab Emirates (UAE), which is situated in the Arabian Gulf. A national programme for cervical cancer screening is likely to be implemented in the future. In this study, we assessed the knowledge, attitude, and practice of UAE female primary care physicians of cervical screening through a self-administered questionnaire. Of the 98 physicians who participated in the study only 40% reported ever having performed a Pap smear. In the study, we identified vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
3
22
0
Order By: Relevance
“…As a predictor of the existing medical infrastructure in UAE, the crosssectional KAP survey 5 showed results that of the 95 of 98 physicians who responded to the question whether they had performed a Pap smear, 38 (40%) stated that they had. The research team had to provide training for the study and other material needed for screening.…”
Section: Logistics Of the Studysupporting
confidence: 85%
“…As a predictor of the existing medical infrastructure in UAE, the crosssectional KAP survey 5 showed results that of the 95 of 98 physicians who responded to the question whether they had performed a Pap smear, 38 (40%) stated that they had. The research team had to provide training for the study and other material needed for screening.…”
Section: Logistics Of the Studysupporting
confidence: 85%
“…Barriers to breast examinations is a subscale of the health beliefs questionnaire [20,21]. The Arabic version of the questionnaire was used in two previous studies, [2,10] in which internal consistency of the subscale was 0.92 and 0.89.…”
Section: Phase 3: Study Phase Methodsmentioning
confidence: 99%
“…In another qualitative study with a small and not representative sample, Muslim-American women reported resisting screening for cervical cancer as it threatened their cultural and religious values [14]. Another study found that out of 98 female primary care physicians in the United Arab Emirates, only 40% reported ever having performed a Pap smear [20]. Presumably rates of attendance for early detection of breast and cervical cancer are increasing among Arab women with the growing number of educational interventions; we were unable to find more accurate studies.…”
mentioning
confidence: 99%
“…One of the main problems of cervical cancer screening in Arab countries is the lack of awareness among health care providers and patients (Badrinath et al, 2004), this combined with the reluctance of women to have internal examination. This in turn resulted in low acceptability and weak uptake of cervical cancer screening, even in countries with available resources.…”
Section: Secondary Preventionmentioning
confidence: 99%